Mechanics of Posterior Stabilized Total Knee Arthroplasty During Daily Activities in Relation to Prosthesis Condylar and Post-cam Design: A Finite Element Study / Mohd Afzan Mohd Anuar and Mitsugu Todo - Mohd Anuar, Mohd Afzan; Todo, Mitsugu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The mechanic of TKA prosthesis in relation to prosthesis design remains unclear despite of previous extensive research. This study attempts to observe the stress states and contact mechanics of polyethylene (PE) insert of knee prosthesis during common daily activities and their relation with condylar and post-cam design. Knee joint loadings during walking, stair climbing, chair sitting and deep squatting were applied to Scorpio Superflex and Scorpio Non-Restricted Geometry (NRG) knee implants using 6-degree-of-freedom (DOF) displacement-force driven model. Finite element models were developed in FEMAP using tetrahedron elements while motions of knee joint were modelled in LS-DYNA. Design of Superflex serves relatively good conformity but more rotational resistance that leads to surface distortion. NRG, however, has more relaxed geometry without compromising the needs of appropriate conforming articular surfaces. This research demonstrated that PE tibial insert stress conditions are closely associated with condylar and post-cam geometry. Conforming interfaces serve good wear resistance, however provide surface constraint towards motion, which leads to surface distortion.